Flavonoid GL-V9 suppresses development of human hepatocellular cancer cells by inhibiting Wnt/β-Cantenin signaling pathway - Ye Gu; Qiaoxian He; Lu Xie; Fangfang Chen; Hangbin Jin; Lilan Lou; Xiaofeng Zhang (Discover Oncology)
Abstract Distant metastasis and post-operative recurrence of tumours are the main causes of death in patients with hepatocellular carcinoma (HCC). In recent years, flavonoids have been found to achieve effective anticancer effects by inhibiting cancer cell proliferation and inducing apoptosis, inhibiting cancer cell invasion and metastasis and neovascularization. GL-V9 is a newly synthesized flavonoid that has been demonstrated anticancer effects in a variety of tumors, but its anticancer effects in HCC and its related mechanisms are still unclear. In this study, we investigated the anti-proliferative, anti-invasive and anti-migratory activities of GL-V9 in HCC cells by MTT method cell proliferation assay, plate cloning assay, transwell invasion assay and cell scratching assay. Based on the results, we found that GL-V9 inhibits the EMT process through a pathway that inhibits Wnt/β-Cantenin pathway signaling, thereby reducing the proliferation, migration and invasion ability of HCC cells. Therefore, GL-V9 may be a novel potential therapeutic agent to inhibit HCC cell metastasis.